Implementation of Art Learning from Waste Plastic Bags in Kindergarten - Citrowati, Endang; Irmawati; Helena (Al-Kahfi: Jurnal Pendidikan Agama Islam, 2024)
Based on observations among the people of West Pasaman Regency, the use of single-use plastic bags is still common. This results in the accumulation and disposal of plastic waste, which can damage the landscape and the environment, spread disease, cause flooding, and damage ecosystems and biota on land, rivers, and the sea. In kindergartens, teachers are observed to be less than optimal in implementing art-making lessons in the form of crafts. Therefore, this study focuses on the implementation of art lessons using used plastic bags at Melati Kindergarten in West Pasaman Regency. This is a mixed methods study using a quantitative approach. This study employed an explanatory mixed methods design, employing sequential quantitative and qualitative research methods. The results of this study, based on qualitative data, had a score of 86%. Qualitative results, using observation, interviews, and documentation, examined the use of used goods, their artistic value, and learning media.